2019
DOI: 10.1007/s12078-019-09275-7
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Valence and Arousal in Subjective Odor Experience

Abstract: IntroductionThe main purpose of this study was to investigate the overall relation between the mean (at the nomothetic or group level) subjective valence and arousal ratings for odors. Although well established in other sensory modalities (e.g., visual, auditory, gustatory, tactile), this relation has not previously been investigated for odors covering a large range of the valence dimension. In addition, we evaluated the EmojiGrid (a recently introduced intuitive graphical affective self-report tool) for the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 111 publications
0
12
0
Order By: Relevance
“…They are also indebted to Prof Duncan Brumby (University College London) for his thoughtful suggestions and helpful comments on an earlier draft of this paper. Part of this work has previously been presented as a poster at the EuroVR 2019 conference in Tallin, Estland, 23-25 October, 2019 (Toet et al, 2019a).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…They are also indebted to Prof Duncan Brumby (University College London) for his thoughtful suggestions and helpful comments on an earlier draft of this paper. Part of this work has previously been presented as a poster at the EuroVR 2019 conference in Tallin, Estland, 23-25 October, 2019 (Toet et al, 2019a).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…In previous studies we found that users were intuitively able to use the EmojiGrid to report their food-evoked emotions (Kaneko et al, 2018;Toet et al, 2018). The EmojiGrid has been extensively validated with different age groups, nationalities, and ethnicities for a range of different affective stimuli (Kaneko et al, 2018;Toet et al, 2018Toet et al, , 2019aToet and Van Erp, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The full set of stimuli is described in more detail elsewhere (Kaneko et al, 2018;Toet et al, 2018) and is also available online (https://osf.io/cyqg7/download). The set of food images were selected such that their associated mean valence (as determined in earlier studies, see Toet et al, 2018Toet et al, , 2019a are distributed along the entire scale (ranging from very low valence for rotten, moulded or contaminated food, via neutral for raw onions, boiled eggs or potatoes, to very high valence for fresh fruit, chocolates and pastries). The 10 additional food images from the validated FRIDa database were selected such that their associated valence scores (as reported in their accompanying data file, see Foroni et al, 2013) also cover a large part of the scale.…”
Section: Methodsmentioning
confidence: 99%
“…One future application of the proposed architecture could be incorporating potential non-invasive actuation effective in regulating arousal state in the real-life human-in-the-loop scenarios. The examples of these actuation are listening to music [85]- [88], adjusting the light in workplaces [89]- [91], smelling fragrances [92]- [94], and drinking beverages such as coffee, tea, and water [95]. Using different actuators and wearable devices, one may perform system identification and model the actuation dynamics [96]- [100].…”
Section: Future Directionsmentioning
confidence: 99%